Specters from 1987: Retromaniac Queer Loneliness in Andrew Haigh’s Estranei (All of Us Strangers, 2023) - Antonio Angelozzi (Cinergie)
This paper aims to examine the spectral nature of queerness through an analysis of the movie Estranei (All of Us Strangers, 2023) by Andrew Haigh, viewed in comparative perspective with its hypotext novel Estranei (Ijintachito no natsu, 2005 [1987]) by Taichi Yamada. In the movie, as Adam interacts with the spectral entities of his parents, deceased during Christmas 1987, and his lover Harry, he melancholically slips into a retromaniac space, accompanied by the songs selected for the movie’s soundtrack – spectral melodies predominantly from the years 1984-87. Adapting a strictly heterosexual text, Haigh’s movie employs queerness as a device of semantic stratification, endowing elements already present in the hypotext – loneliness and disrupted temporality – with new queer meanings and functions. Simultaneously, at the intersection of the trauma of loss and the discomfort of the queer subject in heteronormative society, spectrality is used as a category to describe the very condition of queerness.